Effect of Curcuminoid versus Diclofenac Sodium on Monocytes Secretion of Tumor Necrosis Factor–α in Knee Osteoarthritis - Vivin Hudiyanti (Acta Interna The Journal of Internal Medicine, 2012)
ABSTRACTBackground. Tumor Necrosis Factor-α (TNF-α), a pro-inflammatory cytokine produced by monocyte is increased in osteoarthritis synovial fluid. Curcuminoid from Curcuma domestica Val. suppresses the secretion of TNF-α.Objective. The purpose of this study was to investigate the suppression effect of curcuminoid from Curcuma domestica Val on synovial fluid monocyte’s TNF-α secretion compared to diclofenac sodium in knee osteoarthritisMethods. A prospective randomized open end blinded evaluation (PROBE) method was applied. Subjects were patients with knee osteoarthritis visiting Rheumatology Clinic Dr. Sardjito Hospital and Wirosaban Hospital Yogyakarta. Curcuminoid 30 mg three times daily or diclofenac sodium 25 mg three times daily were administered for 4 weeks. The level of TNF-α secreted by synovial fluid’s monocytes were measured by ELISA before and after treatment.Results. A total of 80 subjects were enrolled, 39 subjects on curcuminoid treatment groups and 41 subjects on diclofenac sodium group. Seven subjects were dropped out, 5 from the curcuminoid group and 2 from the diclofenac sodium group. There was a significant decrement of TNF-α level during 4 weeks treatment in both groups (p< 0.001 respectively). There was no significant difference on TNF-α levels between groups (p= 0,237), neither in 50% decrement of TNF-α levels (p= 518).Conclusion. The effect of curcuminoid in decreasing TNF- α level on patients with osteoarthritis is similar with sodium diclofenac. Keywords: osteoarthritis-monocyte-TNF-α-curcuminoid-diclofenac sodium